2021
DOI: 10.3390/pharmaceutics13091369
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments to Achieve an Efficient Chitosan-Based DNA Vaccine Delivery System

Abstract: In current times, DNA vaccines are seen as a promising approach to treat and prevent diseases, such as virus infections and cancer. Aiming at the production of a functional and effective plasmid DNA (pDNA) delivery system, four chitosan polymers, differing in the molecular weight, were studied using the design of experiments (DoE) tool. These gene delivery systems were formulated by ionotropic gelation and exploring the chitosan and TPP concentrations as DoE inputs to maximize the nanoparticle positive charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Moreover, reducing the CS volume from 4 to 3 mL, a decrease in PDI value is observed from 0.34 to 0.25, as shown in Figure 2 C. When the TTP concentration is reduced, the same effect is noticed, a decrease from 0.39 to 0.32 in PDI values, which means more monodisperse nanoparticles are obtained. The negative impact of higher TPP concentration on PDI was also observed by Rodolfo and colleagues, which concluded that this parameter should be controlled because it is directly related to aggregation phenomena [ 31 ].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Moreover, reducing the CS volume from 4 to 3 mL, a decrease in PDI value is observed from 0.34 to 0.25, as shown in Figure 2 C. When the TTP concentration is reduced, the same effect is noticed, a decrease from 0.39 to 0.32 in PDI values, which means more monodisperse nanoparticles are obtained. The negative impact of higher TPP concentration on PDI was also observed by Rodolfo and colleagues, which concluded that this parameter should be controlled because it is directly related to aggregation phenomena [ 31 ].…”
Section: Resultsmentioning
confidence: 72%
“…The same pattern was observed by Rodolfo and co-authors, since with the increase in TPP concentration and volume, the zeta potential decreased in all CS polymers used. Their work showed that TPP could be responsible for decreasing the zeta potential values due to the increment of the global negative charge of the system [ 31 ]. The positive surface charge of carriers is a very important requirement to improve the cell uptake, and consequently reach an efficient gene delivery system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, chitosan is soluble in acidic environments and has adhesive properties. The excellent adhesion of chitosan reduces the nasal clearance of the vaccine [ 58 , 59 , 60 ]. Chitosan can prolong the retention time of drugs or vaccines and improve their efficacy.…”
Section: Nanovaccinesmentioning
confidence: 99%
“…Response surface methodology and statistical experimental design approaches, such as Box–Behnken designs, are well-suited to identify the optimal polyplex assembly parameters for obtaining uniform, narrowly sized polyplexes that encapsulate their payloads efficiently . Other groups have also investigated the roles of the pH value of the formulation buffer chosen, , cationic polymer molecular weight, and polymer concentration within a DoE framework to rapidly optimize polyplex assembly conditions. Manickam and co-workers optimized self-assembly parameters for polyplexes comprising pDNA and diblock copolymers and found that the pDNA dose and N/P ratio were critical in ensuring efficient delivery of apoptosis-inducing factors to glioblastoma cells …”
Section: Data-driven Design Of Polymeric Vectorsmentioning
confidence: 99%